Influences on teachers' use of participatory learning strategies in health education classes. (November 2014) - Cahill, Helen; Coffey, Julia; Lester, Leanne; Midford, Richard; Ramsden, Robyn; Venning, Lynne
Objective: Participatory learning strategies are integral to the effectiveness of school-based health education programmes; however, use of such methods is not the norm in teaching. The omission of participatory learning strategies is a common form of programme breakdown leading to erosion of positive learning and behavioural outcomes. Based on a survey of 75 Australian high school health education teachers, the study's objective is to examine teachers' perspectives on the factors that influence their use of participatory learning strategies. Results: Whilst it is often presumed that training is the most significant factor, this study found that teachers identify understanding the educational rationale for the approach, student engagement, confidence in class control, and having positive relationships with the students, along with practicalities such as having time to adequately prepare a class, as the most significant influences on their pedagogical choices. Conclusion: The study concludes that a better understanding of the reasons why teachers make particular choices in their delivery of programmes gives valuable insight into what teachers need in order to support uptake or maintenance of such approaches. This understanding may in turn contribute to health education programmes being delivered with a higher fidelity and better outcomes for students.